CrowdWalk: Leveraging the wisdom of the crowd to inspire walking activities - Ornelas, Tiago; Caraban, Ana; Gouveia, Rúben; Karapanos, Evangelos (My University, 2015)
Despite the initial premise of activity trackers, recent work has questioned their long-term efficacy in supporting behavior change. This paper makes two contributions. First, we present a study that inquired into individuals' ways of incorporating physical activity into their daily routines - and specifically, the "why, how, when and where" of physical activity. Secondly, we present CrowdWalk, a mobile app that leverages the wisdom of the crowd to produce location-based "walking challenges", and thus attempts to assist behavior change through highlighting opportunities for physical activity.
Keywords: Activity tracking; Behavior change; Crowdsourcing; Persuasive technologies; Self-quantification